The Association of Maternal Exposure to Domestic Violence During Childhood With Prenatal Attachment, Maternal-Fetal Heart Rate, and Infant Behavioral Regulation - Sancho-Rossignol, Ana; Schilliger, Zoe; Cordero, María I.; Rusconi Serpa, Sandra; Epiney, Manuella; Hüppi, Petra; Ansermet, François; Schechter, Daniel S. (Frontiers in Psychiatry, 2018)
Human and animal models suggest that maternal hormonal and physiological adaptations during pregnancy shape maternal brain functioning and behavior crucial for offspring care and survival. Less sensitive maternal behavior, often associated with psychobiological dysregulation and the offspring’s behavioral and emotional disorders, has been observed in mothers who have experienced adverse childhood experiences. Strong evidence shows that children who are exposed to domestic violence (DV) are at risk of being abused or becoming abusive in adulthood. Yet little is known about the effect of childhood exposure to DV on the expecting mother, her subsequent caregiving behavior and related effects on her infant. Thus, the present study examined the association of maternal exposure to DV during childhood on prenatal maternal attachment, maternal heart rate reactivity to an infant-crying stimulus and post-natal infant emotional regulation. Thirty-three women with and without exposure to DV during childhood were recruited during the first trimester of pregnancy and followed until 6-month after birth. The Maternal Antenatal Attachment Scale (MAAS) was used to measure prenatal attachment of the mother to her fetus during the second trimester of pregnancy, maternal and fetal heart rate reactivity to an infant-crying stimulus was assessed at the third trimester of pregnancy, and the Infant Behavior Questionnaire-Revised (IBQ-R) was used to assess infant emotional regulation at 6-months. Results showed that pregnant women that were exposed to DV during childhood had a poorer quality of prenatal attachment of mother to fetus, regardless of whether they also experienced DV during adulthood. In addition, maternal exposure to DV during childhood was associated with increased maternal heart rate to infant-crying stimulus and worse infant emotional regulation. These findings highlight the importance of prenatal screening for maternal exposure to DV during childhood as a risk factor for disturbances in the development of maternal attachment, dysfunctional maternal behavior and infant emotion dysregulation.